Utilization of forest plant resources by the local people around Kalinzu Forest Reserve, South-Western Uganda - Omucunguzi, Adalbert Aine; Rugunda, Grace Kagoro; Byarugaba, Dominic (Blackwell Publishing Ltd, Afr. J. Ecol, 2009)
Local communities depend on Kalinzu Forest Reserve (KFR) for plant resources (Appendix 2). This resource utilization affects the forest ecosystem. The frequency and methods of harvest were studied to assess the impact of plant resource utilization in Kalinzu. The forest supports twelve species endemic to it. These include nine butterfly species, one mammalian species and two tree species. This study documented the plant resources harvested, plus fre quency, quantities and mode of harvest, to make recommen dations that can encourage sustainable forest resource use. Observation and interviews with resource harvesters were used to identify plant products harvested and the species from which they were harvested. Interviews were held with heads of randomly selected households to obtain more information about plant products harvested from the forest. The frequency of resource harvest was determined by noting the number of people that harvested a particular resource on each day of harvest. Kalinzu Forest Reserve occupies parts of the counties of Bunyaruguru, Ruhinda and Igara in Bushenyi district south-western Uganda, with a population density of 328 persons km)2 . It was gazetted for a reserve in 1932 with an area of 461 km2 , but some of the land was given off for tea estates development in 1954. The reserve now covers an area of 137 km2 (Howard, 1991). It lies on the eastern side of the Great Western Rift Valley at the edge of the escarpment overlooking Lake Edward. KFR is located between latitude 0 17¢ and 0 30¢N and between 30 00¢ and 30 07¢ E and at an altitude ranging from 1200 to 1500 m above sea level.
Keywords: Utilization; Forest plant resources; Local people; Kalinzu Forest Reserve; Uganda